Legal Protection for the Dominus in Acts of Zaakwarneming - Juliane Irene Tomasoa; Teng Berlianty; Ronald Saija (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2025)
.An incident that often occurs in the life of others is an act without orders from others or voluntary help, this act is called Zaawarneming. Juridical-normative legal research using the Legislation approach, Conceptual approach related to the problem being studied. The findings of this study are that Dominus' protection in the Civil Code includes the Manager's obligation to account for its actions, Dominus' right to reject or accept the Manager' s actions, the Manager's obligation to compensate for damages, Dominus not paying wages to the Manager, and Dominus' right to terminate the act of Zaakwarneming. Currently, existing legal rules focus more on regulating the rights and obligations of Dominus (the owner of the interest) without providing sanctions or a clear compensation mechanism for Dominus if the Gestor (the party carrying out the management act) makes a mistake.